Improved particle swarm optimization algorithm for enhanced coupling of coaxial optical communication laser - Duan, Lian; Zhou, Haibo; Tan, Shuaixia; Duan, Ji-an; Liu, Zhixian (Optical fiber technology, 2021)
•The non-linearly decreasing inertia weight is more suitable for three DOF stage alignment.•A new relation between the inertia weight and iteration is established.•The proposed PSO algorithm presents the good performance via simulation and experiment.•The increase of search coefficient can change the global and local search ability in improved PSO algorithm. In this paper, we investigate a novel improved Particle Swarm Optimization (IPSO) algorithm to enhance the coupling precision between a laser diode and a single-mode fiber. It mainly relies on the nonlinear adjustment of inertia weight. Several variations of PSO are used as references. The simulated and experimental results show that the proposed strategy has an excellent search success rate with few iterations in multi-degree of freedom alignment. This is largely due to the improvement of exploration via the adjustment of inertia weight. These results confirm that the improved PSO algorithm can be applied reliably to improve both the efficiency and accuracy in laser-fiber coupling.